FACTORS DETERMINING THE DEMAND FOR AFFORDABLE HOUSING - Lim, Xin Ying; Olanrewaju, Abdul Lateef; Tan, Seong Yeow; Lee, Jia En (PLANNING MALAYSIA, 2018)
Affordable housing has been defined as housing which is adequate in quality and location. In addition to this, it is deemed to be housing that is not so costly that it prevents its occupants from meeting their basic living needs. This study aims to develop a framework to facilitate affordable housing delivery. The data collection used was a survey questionnaire. The survey was administered to occupants within five high-rise buildings in Penang. The study also utilized a Kaiser-Meyer-Olkin measure of 0.518, and Bartlett’s test of sphericity of (x2 (210) = 10953.982, p<0.001). The two statistical test discovered that the major determinants affecting demand for affordable housing were crime rates, housing prices and down payments. The results also demonstrated that six factors were successfully constructed using a factor analysis and assigned as factors that determined the demand for affordable housing. The research will be useful to policy makers, urban planners, developers, and contractors.